Aplikasi Wisata Virtual Pantai Balekambang dan Watu Leter di Malang Raya dengan Lingkungan Suasana Terintegrasi - Alexander Krisna Giri Wicaksono; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Malang is one of the favorite tourist destinations in the country. However, the beaches in South Malang are still relatively deserted by tourists. This is because its location is far from the city center, so most tourists prefer to visit attractions in the city center and Batu area only. In fact, the beaches in South Malang have a beauty and uniqueness that is not widely known by tourists. With the increasing number of facilities and media that support the implementation of virtual reality, the innovation that is widely applied is using virtual tourism. Many companies in the tourism industry innovate by utilizing this digital technology. Innovations using virtual reality in the tourism sector have been shown to have a positive impact. Based on the problems that have been described, a virtual tourism application for Balekambang and Watu Leter Beach in Greater Malang was developed with an integrated ambience environment. In its development, this application uses the Agile software development life cycle (SDLC) and is based on Web VR. This application is divided into two parts, a VR application for users, and an admin application to manage data on tourist attractions and spots that will be used by users. The implementation of this application uses HTML, CSS, PHP, and Javascript. HTML and CSS are used to create views with the help of Bootstrap. PHP and Javascript are used to run application functions with the help of Laravel and A-Frame. This application was tested using black box testing method for functional requirements, as well as usability and compatibility testing for non-functional requirements. From the results of black box testing, it was found that all functional requirements were valid. From the results of usability testing, it was found that VR applications without an ambience environment got an average System Usability Testing (SUS) score of 70.42, VR applications with an ambience environment got an SUS score of 80.83, and admin applications got an SUS score of 72.5.